2022
DOI: 10.4236/jss.2022.1010008
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the Sexually Abused Street Children. A Case of One of the Cities in Tanzania

Abstract: This study is about the experiences of the sexually abused street children in one of the cities in Tanzania. The study makes use of the data from 34 respondents. A questionnaire, in-depth interviews and focus group discussions were used to collect data. The findings show that the sexually abused street children have experienced all types of sexual encounters, with rape and sodomy being the common type of sexual abuse. The maximum number of times an individual child has been sexually abused is 9 times and a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 107 publications
1
2
0
Order By: Relevance
“…The finding of the study also illustrated that homeless youth suffered from a combination of lower selfesteem, trauma, depression, and addiction on the street (Lockhart, 2008;Mathebula and Rossa, 2013). Consistent with previous studies (Abebe, 2009;Abebe, 2008;Demewozu, 2005;Ally and Paul, 2022;Fantahunand Taa, 2022), homeless youth participated in this study reported begging and survival sex as their livelihood strategy despite shameful activities. Homeless young women are coerced into having survival sex, in which sex is sold as a commodity in exchange for cash and food.…”
Section: Dscussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding of the study also illustrated that homeless youth suffered from a combination of lower selfesteem, trauma, depression, and addiction on the street (Lockhart, 2008;Mathebula and Rossa, 2013). Consistent with previous studies (Abebe, 2009;Abebe, 2008;Demewozu, 2005;Ally and Paul, 2022;Fantahunand Taa, 2022), homeless youth participated in this study reported begging and survival sex as their livelihood strategy despite shameful activities. Homeless young women are coerced into having survival sex, in which sex is sold as a commodity in exchange for cash and food.…”
Section: Dscussionsupporting
confidence: 88%
“…Living on the streets endangers young people in low-income countries such as Ethiopia. On the streets, homeless youth face numerous social and health problems including social marginalization, stigma, violence, poor health, hostility of the public, psychological trauma, victim criminalization, and sexual assault (Abebe, 2009;Ally and Paul, 2022;Bourdillon, 1994;Lockhart, 2008;Mathebula and Ross, 2013;Tyler and Melander, 2015). Evidence indicated that begging, petty theft, survival sex, and vendor can be used as means of a living by homeless youth (Abebe, 2008;Demewozu, 2005;Fantahun and Taa, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Vameghi et al (2023) and UNICEF (2020) suggested that street children are among the most marginalized globally, experiencing severe violations of their rights and facing multiple deprivations. Ally and Paul (2022) resolutely affirmed that street children are highly vulnerable and frequently at risk, especially of sexual abuse and exploitation. Kaplan and Çuhadar (2020) proposed that children become homeless and engage in labor due to various factors, including family dynamics, socioeconomic conditions, and peer pressure, with variations observed between industrialized and developing countries.…”
Section: Challenges Faced By Street Childrenmentioning
confidence: 99%